2015
DOI: 10.1039/c5nr04551g
|View full text |Cite
|
Sign up to set email alerts
|

Highly flexible transparent self-healing composite based on electrospun core–shell nanofibers produced by coaxial electrospinning for anti-corrosion and electrical insulation

Abstract: Coaxial electrospinning was used to fabricate two types of core-shell fibers: the first type with liquid resin monomer in the core and polyacrylonitrile in the shell, and the second type with liquid curing agent in the core and polyacrylonitrile in the shell. These two types of core-shell fibers were mutually entangled and embedded into two flexible transparent matrices thus forming transparent flexible self-healing composite materials. Such materials could be formed before only using emulsion electrospinning,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 44 publications
1
63
0
Order By: Relevance
“…This work was focused more on C/S fibers production without further investigation on healing performance and recovering efficiency. Recently, Lee and coworkers carried out the electrospinning of self‐healing composites and coatings by encapsulating DMS in PAN . Neisiany et al .…”
Section: C/s Nanofibersmentioning
confidence: 99%
“…This work was focused more on C/S fibers production without further investigation on healing performance and recovering efficiency. Recently, Lee and coworkers carried out the electrospinning of self‐healing composites and coatings by encapsulating DMS in PAN . Neisiany et al .…”
Section: C/s Nanofibersmentioning
confidence: 99%
“…The three-electrode system consisted of the coating on steel for the working electrode, a Pt counter electrode, and a Ag/AgCl reference electrode. Each specimen was exposed to a freshly prepared aqueous salt solution (5% NaCl, 30…”
Section: Electrochemical Analysis Of Coatingmentioning
confidence: 99%
“…Without confirmation that the healing agents successfully reacted, the coatings may have only unreacted (liquid) healing agents in the damage region, which acts only as a temporary physical barrier between the metal substrate and the environment. Electrospinning has also been used to develop flexible transparent self-healing coatings for optical devices [30]. In addition to coatings, electrospun fibers have also been used to add healing functionality into composites [11,[31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al reported that a blend solution of Poly(vinylidene fluoride) (PVDF) and polyethylene oxide (PEO) had a good effect on encapsulating the reactive DMS and its healing agents [ 24 , 25 ]. Unfortunately, much room for improvement remains for traditional working processes, such as layered electrospinning and double coaxial electrospinning [ 26 ], in terms of facile preparation, accurate loading of the healing and curing agents, and utilization efficiency. Most recently, Yildiz et al used three-fluid electrospinning to prepare self-healing materials.…”
Section: Introductionmentioning
confidence: 99%